The language of the land - Rabhi, Pierre (Technical Centre for Agricultural and Rural Cooperation, 1988)
Pierre RabHi An author and educator, Pierre Rabhi was born in the Sahara and has been farming in the Ardeche region of France since 1960. The desert survival skills of Pierre Rabhi led him to apply organic farming methods based on compost to...